Relationship Between Student Social Interaction and Teacher with Student Learning Motivation - Alvino Sanovan; Mudjiran Mudjiran (Jurnal Neo Konseling, 2019)
Individual who have motivation to learn are individuals who have an awareness off the abilities that are in him, and he is able to increase the motivation they have. Important learning motivation for student, so that learning is succesful in the learning process. Motivation to learn is one of them that is motivated by social interaction. This study is intended to discuss the social relations of student and student learning teacher at Adabiah High School Padang. This research is a descriptive correlational research with quantitative methods. Taking samples in this study using stratified random sampling with a total sample of 2019 students. The research instrumens used were questionnaires for social interaction and learning motivation. The result of the study revealed that (1) students and teacher social interaction in Adabiah Padang high school was in a good category, (2) studenst motivation in high school Adabiah Padang was in the high category, (3) there was a significant relationship between student’s and teacher’s social interactions with learning motivastion student’s in Adabiah Padang.